ETIKA GURU DAN MURID DALAM TARIKAT SAMMANIYAH - Sya'rani, Ahmad (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2016)
Sheikh Muhammad Samman who love science and adrift heart of the religious sciences, devoted himself to God directly in the path of Sufism. Because of his persistence in the world of mysticism, it leds Sheikh Muhammad Samman to various teachers and sheikhs, until he also founded a new tarikat which is a combination of various tarikat that he followed previously. The emergence of a new tarikat that is based on some tarikat is not new and can be accepted. Surely, he formed a new tarikat called Sammaniyah that have many followers until now. Of his teachings in the tarikat, there are some rules that discussed about relationship between the Murshid or sheikh with a pupil. The concept about it is similar to the relationship between the Prophet with his companions or with some of his followers. From Sirah Nabawiyah, it can be concluded how the Companions of the Messenger had spoken and vice versa as well as he, the Prophet., treats his companions. Actually, this condition applies to every tarikat anywhere.